Differential contribution of PBP occupancy and efflux on the effectiveness of β-lactams at their target site in clinical isolates of Neisseria gonorrhoeae. - Silvia López-Argüello; Eva Alcoceba; Paula Ordóñez; Biel Taltavull; Gabriel Cabot; Maria Antonia Gomis-Font; Antonio Oliver; Bartolome Moya (PLoS Pathogens)
Neisseria gonorrhoeae exhibits alarming antibiotic resistance trends and poses a significant challenge in therapeutic management. This study aimed to explore the association of penA alleles with penicillin-binding protein (PBP) occupancy patterns and reduced outer membrane permeability, impacting susceptibility to last-line cephalosporins and potential β-lactam candidates. The whole genome sequence, the MICs and PBP IC50s were determined for 12 β-lactams and β-lactamase inhibitors in 8 clinical isolates with varying β-lactam sensitivity, 2 ATCC, and 3 WHO cephalosporin-resistant reference strains. The genetic analysis identified diverse determinants of β-lactam resistance including penA, ponA, porB, and mtrR alterations. Mosaic penA alleles were confirmed to be key determinants of cephalosporin resistance, with notable impacts on PBP2 IC50 affinities (in the presence of all PBPs). Substitutions in positions V316 and A501 exhibited significant effects on β-lactam PBP2 occupancy and MICs. PBP1 inhibition showed marginal effect on β-lactam sensitivity and PBP3 acted as a sink target. Ertapenem and piperacillin emerged as potential therapies against cephalosporin-resistant N. gonorrhoeae strains, along with combination therapies involving tazobactam and/or efflux inhibitors. The study determined the β-lactam PBP-binding affinities of last-line cephalosporins and alternative β-lactam candidates in strains carrying different penA alleles for the first time. These findings provide insights for developing new antimicrobial agents and enhancers against emerging resistant strains. Further research is warranted to optimize therapeutic interventions for cephalosporin-resistant N. gonorrhoeae infections.